Rozwój przemysłu cynkowego w Królestwie Polskim w latach 1815-1904 - Kowalczyk, Rafał Wiktor (Acta Universitatis Lodziensis. Folia Historica, 2005)
Development or zinc industry took place in The Kingdom of Poland at the beginning of XIX century. It was caused by significant increase of demand Tor zinc mainly in industrialized countries of Western Europe. Since 1815 government of The Congress Kingdom started to develop this industry on the area of Zagłębie Dąbrowskie. Particular initiative in this development was manilested by prince Ksawery Drucki-Lubecki. Investments of the treasury caused dynamic development of zinc industry in Zagłębie Dąbrowskie. It was significant for development of coal mining in The Congress Kingdom. However, world economical crisis at the end of the 1820s ended good period for zinc in Western Europe. Also, economical effects of the uprising in 1931 changed government politics concerning zinc industry. After the uprising government’s plans of development of metallurgical infrastructure at the area of Zagłębie Dąbrowskie failed. Private initiative of development of zinc industry by Piotr Steinkeller was a fiasco too. Only building of Warsaw-Vienna railroad and its part leading to Górny Śląsk in 1859 caused development of inner market, inflow of foreign investments in heavy industry and breaking of stagnation in Zagłębie Dąbrowskie. But only change of economical doctrine in 1877 caused real development of zinc industry in The Kingdom of Poland. In 1860s begun process of penetration of zinc beds in Zagłębie Dąbrowskie by German capital from Górny Śląsk. Its first investor was Gustaw von Kramst. The amount of capital invested in von Kramst’s factory let to achieve high profits and to distance form government’s mines of galman ore. It was a fact despite richer ore deposits in government’s mines. Main problem in von Kramst’s enterprise was necessity of increasing of galman ore extraction. There were major financial losses because of mechanical mines draining. As a result „Gwarectwo von Kramsta” sold its mines and factories to French investor „Tow. Sosnowieckie”. Renting of government’s galman mines and steelworks „Pod Będzinem" to P. P. Derwisz, A. A. Pomerancew and M. M. Szewcow’s heirs company changed situation of zinc industry in The Kingdom of Poland. „Dzierżawcy rządowych zakladóww górniczych w Królestwie Polskim” company dynamically developed its infrastructure and distanced „Tow. kopalń i zakładów hutniczych Sosnowieckich”. It was caused by different strategy of „Dzierżawcy" rządowych zakładów górniczych w Królestwie Polskim” and „Tow. kopalń i zakładów hutniczych Sosnowieckich”. "Tow. kopalń i zakładów hutniczych Sosnowieckich” wanted to take over all mining companies owned by German capital and to dominate in mining and metallurgical industry in Zagłębie Dąbrowskie. Zinc industry was taken by „Tow. Sosnowieckie” as a result of taking over mines and factories of „Tow. górniczo-hutnicze von Kramsta”. However, crisis in this industry caused financial problems in „Dzierżawcy rządowych zakładów górniczych w Królestwie Polskim" company and its bankrupcy. „Tow. Francusko-Rosyjskie” which took over „Dzierżawcy rządowych zakładów Górniczych w Królestwie Polskim” company belonged to French group managing „Société Anonyme des Forges et Acieries de Huta Bankowa” and „Tow. górniczo- -przemysłowe hr. Renard”. Good management and modernization increased productivity. As a result, „Tow. Francusko-Rosyjskie” reached maximum development despite exploatation of poor deposits of zinc silicat in The Kingdom of Poland. In 1907 „Tow. Francusko-Rosyjskie” mined 84,40% of galman ore and produced 60,49% of zinc. Poor deposits of galman ore had negative influence to zinc industry. It slowed down development of „Tow. kopalń i zakładów hutniczych Sosnowieckich” and „Tow. Francusko-Rosyjskie”. The content of metallic zinc in galman ore in Zagłębie Dąbrowskie was average 50% but because of contamination it was only about 14%. On the other hand, high duties and monopolization of zinc mining on Górny Śląsk by a few potentates had negative influence on export of zinc to The Kingdom o f Poland. That is why zinc industry did nod achieve its pre- 1904 level.